Association of sprint performance with ground reaction forces during acceleration and maximal speed phases in a single sprint - Nagahara, R.; Mizutani, M.; Matsuo, A.; Kanehisa, H.; Fukunaga, T. (Journal of Applied Biomechanics, 2018)
We aimed to clarify the mechanical determinants of sprinting performance during acceleration and maximal speed phases of a single sprint, using ground reaction forces (GRFs). While 18 male athletes performed a 60-m sprint, GRF was measured at every step over a 50-m distance from the start. Variables during the entire acceleration phase were approximated with a fourth-order polynomial. Subsequently, accelerations at 55%, 65%, 75%, 85%, and 95% of maximal speed, and running speed during the maximal speed phase were determined as sprinting performance variables. Ground reaction impulses and mean GRFs during the acceleration and maximal speed phases were selected as independent variables. Stepwise multiple regression analysis selected propulsive and braking impulses as contributors to acceleration at 55%-95% (ß>0.72) and 75%-95% (ß>0.18), respectively, of maximal speed. Moreover, mean vertical force was a contributor to maximal running speed (ß=0.48). The current results demonstrate that exerting a large propulsive force during the entire acceleration phase, suppressing braking force when approaching maximal speed, and producing a large vertical force during the maximal speed phase are essential for achieving greater acceleration and maintaining higher maximal speed, respectively.